Macro- and microclimate conditions lead to rapid grapevine deacclimation: evidences of thermal amplitude incidence from two contrasting wine regions from North and South America - Gonzalez Antivilo, Francisco (2017)
Low temperature is a limiting factor that affects vineyard distribution globally. The level of cold hardiness acquired during the dormant season by Vitis sp. is crucial for winter survival. Most research published on this topic has been generated beyond 40° N latitude, where daily mean temperatures may attain injurious levels during the dormant season resulting in significant damage to vines and buds. Symptoms of cold injury have been identified in Mendoza (32–35° S latitude), a Southern Hemisphere wine region characterized by a high thermal amplitude, and warm winds during the dormant season. These symptoms have usually been attributed to drought and/or pathogens, but not to rapid deacclimation followed by injurious low temperatures. Because local information on meteorological events as probable causes is scarce, this research was designed to test and study this assumption by comparing macro-, meso-, and microclimatic data from Mendoza, Argentina, and eastern Washington, USA. The goal was to unveil why freezing damage has occurred in both regions, despite the existence of large climatic differences. Because environmental parameters under field conditions may not correspond to data recorded by conventional weather stations, sensors were installed in vineyards for comparison. Microclimatic conditions on grapevines were also evaluated to assess the most vulnerable portions of fieldgrown grapevines. In order to better understand if it may be possible to modify cold hardiness status in a short period with high thermal amplitude conditions, deacclimation was induced using a thermal treatment. Hence, despite the fact that Mendoza is warmer, and temperatures are not as extreme as in Washington, high daily thermal amplitude might be partially involved in plant deacclimation, leading to a differential cold hardiness response.